AB1219-HPR Predictive Ability of Coping Perception on Quality of Life in Asian Rheumatoid Arthritis Patients. (9th June 2015) - Chew, E.; Griva, K.; Cheung, P.
Abstract : Background: In coping with chronic illnesses such as rheumatoid arthritis (RA), patient's perceptions of their coping effectiveness can influence on their choice of coping styles [1]. We have identified 5 coping styles used by Asian RA patients: active problem solving, distancing, cognitive reframing, emotional expression and self-reliance; with the latter 2 associated with poorer quality of life (QOL). Objectives: To examine the relationship of coping perception with coping styles adopted by Asian RA patients and its associations with quality of life (QOL) over 6 months. Methods: Consecutive adult patients with established RA (ACR 1987) at a tertiary hospital in Singapore were assessed at two time points: baseline and at 6 months. Data collected included demographics, coping styles (Coping with Rheumatoid Arthritis Questionnaire (C-RAQ)), and level of coping perception (coping effectiveness and helplessness on a numerical rating scale from 0-10). Disease activity (disease activity score of 28 joints (DAS28)), impact of disease (Rheumatoid Arthritis Impact of Disease, RAID), physical QOL (SF12PCS) and mental QOL (SF12MCS) were obtained at baseline and 6 months. Statistical analyses included: (i) Relationship of coping perceptions and coping styles: Spearman Rho (baseline), (ii) Association of coping perceptions and styles with QOL: Hierarchical Regression (baseline and 6 months). Results: Of the 101 patients included, 72.3% were Chinese, 11.9% Malay and 11.9% Indian. Mean age was 54.2±12.6 years, 81.2% were females, and disease duration was 7.3±7.7 years. At baseline, the mean DAS28 was 3.4±1.2, RAID was 2.5±2.0, SF12PCS was 42.7±9.4, and SF12MCS was 51.2±8.9. At 6 months, the mean DAS28 was 3.1±1.1 RAID was 2.1±2.1, SF12PCS was 45.6±8.1, and SF12MCS was 52.4±9.8. Active Problem Solving correlated with coping effectiveness ( r =0.25, p =0.004), while Self-Reliance and Emotional Expression correlated with helplessness ( r =0.35 and r =0.40 respectively, p <0.01 for both). At baseline, helplessness was associated with poorer physical QOL (β=-0.25, p =0.04), adjusted for the following covariates: DAS28, body mass index, coping effectiveness, Emotional Expression and Self-Reliance. Helplessness was also associated with poorer mental QOL (β=-0.29, p =0.02), after adjusting for DAS28, education, smoking status, Emotional Expression and Self-Reliance. Helplessness was associated with higher impact of disease (β=0.55, p <0.001), after adjusting for coping effectiveness and Self-Reliance. At 6 months, the level of helplessness remained predictive of higher impact of disease (β=0.33, p =0.02), after adjusting for DAS28, age, education, Self-Reliance and Emotional Expression. Coping effectiveness was uniquely predictive of better mental QOL (β=0.38, p =0.004), after adjusting for the same covariates. Conclusions: Coping styles of Self-Reliance and Emotional Expression are associated with poorer coping perception. This perception is associated with poorer QOL, and is predictive of subsequent impact of disease. Tailored psychosocial support needs to address not only coping styles themselves, but patient's perception to their level of coping. References: Lorig K, Chastain RL, Ung E, Shoor S, Holman HR (1989). Development and evaluation of a scale to measure perceived self-efficacy in people with arthritis. Arthritis and Rheumatism, 32(1), 37–44. Disclosure of Interest: None declared